2014
DOI: 10.4103/0970-9371.130695
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of giant soft tissue chondroma of the wrist: A cytopathological study with review of the literature

Abstract: Giant soft tissue chondromas (STCs) of the wrist are seldom encountered in clinical practice. Precise diagnosis of benign STC may pose diagnostic difficulties on clinical and radiological findings alone. We encountered a slowly growing soft tissue neoplasm in the radial aspect of the wrist joint of the right hand in a 52-year-old male, masquerading as a calcified hematoma, as suggested by magnetic resonance imaging. On cytohistopathological examination, it turned out to be a rare giant STC. The variable cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Our literature analysis of EC affecting the hand and upper extremity (Table 1) revealed 25 cases reported [2,[4][5][6][7][8][9][10][11][12][13][14][15][16], located in digits (eight cases), within the carpal tunnel (three), or in other sites in the hand (ten); in four cases, information about the exact location was missing. The average size ranged from 0.5 to 12 cm in an estimated diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature analysis of EC affecting the hand and upper extremity (Table 1) revealed 25 cases reported [2,[4][5][6][7][8][9][10][11][12][13][14][15][16], located in digits (eight cases), within the carpal tunnel (three), or in other sites in the hand (ten); in four cases, information about the exact location was missing. The average size ranged from 0.5 to 12 cm in an estimated diameter.…”
Section: Discussionmentioning
confidence: 99%
“…It defines the contour, the extent, the shape, calcification and the relation of the tumour to the surrounding structures. Sometime FNAC or core needle biopsy is required to determine the exact diagnosis preoperatively, especially when the physician worried about malignancy [11] . Even by MRI, this case was query regarding the benign nature of the lesion, the core needle biopsy was not conclusive as well.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, they found that 49% were located at the fingers, 15% at the hands, 11% at the toes, 10% at the feet, 4% at the forearms, and 11% at other sites. ESCs have also been described in the popliteal region [13] , Hoffa's infrapatellar fat [14] , [15] , wrist [16] , elbow joint [17] , while some more rare locations can be the gluteal region [18] , diaphragm [19] , anterior abdominal wall [20] , axilla [21] , scalp [22] , preauricular region [4] , dura [23] , larynx [24] , pharynx [25] , neck [26] , oral cavity [27] , skin [28] , fallopian tube [29] , and parotid gland [30] .…”
Section: Discussionmentioning
confidence: 99%